Relationship between Narcissism, Self-Esteem, and Social Media Addiction in Preclinical Medical Students - Helen Susanto; Eva Suryani; Yunisa Astiarani; Felicia Kurniawan (Faculty of Medicine Universitas Padjadjaran, 2021)
Background: Narcissism is a condition in which people have a constant demand to be complimented and prioritized. Self-esteem is a subjective evaluation of one's worth. Several studies have linked narcissism and low self-esteem as a risk factor of social media addiction, a disorder where individuals displayed an unhealthy compulsion to access social media until it disrupts other activities. This study aimed to discover the relationship between narcissism, self-esteem, and social media addiction in preclinical medical students. Methods: This study was a cross-sectional observational analytical study on 211 preclinical medical students at the Atma Jaya Catholic University of Indonesia. Instruments used in this study were Narcissistic Personality Inventory-16 (NPI-16), Rosenberg Self-Esteem Scale (RSES), and Bergen Social Media Addiction Scale (BSMAS). Data were analyzed statistically using Chi-square in STATA analytic program.Results: Of all respondents, 6.6% were narcissistic, 19.9% had low self-esteem, and 34.6% had social media addiction. There was a significant relationship between narcissism and social media addiction (p=0.021) and between self-esteem and social media addiction (p=0.002).Conclusion: There is a relationship between narcissism, self-esteem, and social media addiction in university students. This indicates the importance of preliminary psychological screening in students, especially regarding self-esteem, narcissism, and social media addiction, to develop approaches that will ensure good academic achievements and physical health among students.